2021
DOI: 10.1002/pros.24247
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of erectile function by a combination of antiapoptosis by JNK inhibitor and preservation of smooth muscle or endothelium by hepatocyte growth factor in a rat model of cavernous nerve injury

Abstract: Background: Because of structural alterations in the corpus cavernosum after radical prostatectomy (RP), post-RP erectile dysfunction remains a very difficult condition to treat. We aimed to determine if the combined administration of a Jun-amino terminal kinase (JNK) inhibitor and hepatocyte growth factor (HGF) in the immediate post-injury period would restore erectile function by antiapoptotic and proregenerative effects through the rectification of molecular pathways related to the structural integrity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…By targeting TGF-β1 signaling as CAV1 does, CSD peptide serves as a signi cant functional replacement for CAV1 and may be involved in the control of multiple pathways [15,16]. While TGF-β1, a signi cant contribution to CNI-ED, can activate Smad, c-Jun N-terminal kinase (JNK), and Rho/ROCK so as to provoke corporal apoptosis [4,[11][12][13][14]. It is uninvestigated if CSD peptide can inhibit the aforementioned signaling pathways to limit CCSMCs apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By targeting TGF-β1 signaling as CAV1 does, CSD peptide serves as a signi cant functional replacement for CAV1 and may be involved in the control of multiple pathways [15,16]. While TGF-β1, a signi cant contribution to CNI-ED, can activate Smad, c-Jun N-terminal kinase (JNK), and Rho/ROCK so as to provoke corporal apoptosis [4,[11][12][13][14]. It is uninvestigated if CSD peptide can inhibit the aforementioned signaling pathways to limit CCSMCs apoptosis and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that CCSMCs from CNI mices and Spinal Cord Injury (SCI) men has higher levels of Smad2 phosphorylation and apoptosis [6,10]. However, targeting TGF-β1 signaling, including Smaddependent and -independent pathways, seems to be highly e cient in avoiding corporal apoptosis, restoring smooth muscle content, and erectile function (EF) in CNI rats [4,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%